2007
DOI: 10.1007/s10519-007-9179-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Serotonergic Genes htr1A, htr1B, htr2A, and slc6A4 in Aggressive Behavior of Golden Retriever Dogs

Abstract: Aggressive behavior displays a high heritability in our study group of Golden Retriever dogs. Alterations in brain serotonin metabolism have been described in aggressive dogs before. Here, we evaluate whether four genes of the canine serotonergic system, coding for the serotonin receptors 1A, 1B, and 2A, and the serotonin transporter, could play a major role in aggression in Golden Retrievers. We performed mutation screens, linkage analysis, an association study, and a quantitative genetic analysis. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 50 publications
0
22
2
Order By: Relevance
“…Individuals with the T161 locus had more lifetime aggressive behaviors, and again this polymorphism was linked to reduced transcriptional activity of 5-HT 1B receptors (Sun et al 2002). However, these associations between the HTR1B polymorphisms (G861C, G261T, or C129T) and aggression and antisocial behavior are not seen in other studies (Huang et al 1999; Kranzler et al 2002; New et al 2001; Sinha et al 2003; Van den Berg et al 2008). Based on the findings from pharmacological studies and gene knockout and polymorphism studies, it is likely that the 5-HT 1B receptor has an important role in the inhibition of certain types of aggression.…”
Section: 5-ht Receptorscontrasting
confidence: 59%
See 1 more Smart Citation
“…Individuals with the T161 locus had more lifetime aggressive behaviors, and again this polymorphism was linked to reduced transcriptional activity of 5-HT 1B receptors (Sun et al 2002). However, these associations between the HTR1B polymorphisms (G861C, G261T, or C129T) and aggression and antisocial behavior are not seen in other studies (Huang et al 1999; Kranzler et al 2002; New et al 2001; Sinha et al 2003; Van den Berg et al 2008). Based on the findings from pharmacological studies and gene knockout and polymorphism studies, it is likely that the 5-HT 1B receptor has an important role in the inhibition of certain types of aggression.…”
Section: 5-ht Receptorscontrasting
confidence: 59%
“…It is possible that polymorphisms that affect the level of expression of 5-HT 2A receptors can be associated with self-directed aggression. In some samples, a significant linkage was found between polymorphisms in the 5-HT 2A receptor (HTR2A) gene, T102C, A1438G and His452Tyr, and aggressive-impulsive trait or adolescent-onset antisocial behavior in humans (Assal et al 2004; Bjork et al 2002; Burt and Mikolaiewski 2008; Nomura et al 2006), but others have reported no such link between aggression and HTR2A polymorphisms (Khait et al 2005; Van den Berg et al 2008). Again, the successful pharmacotherapeutic management of aggressive patients using compounds with affinity for 5-HT 2A receptors would suggest that violence-prone individuals may be characterized by distinctive HTR2A polymorphisms.…”
Section: 5-ht Receptorsmentioning
confidence: 99%
“…Reisner et al (128) reported decreased concentrations of a major metabolite of seratonin in cerebrospinal fluid of dominant aggressive dogs, and Badino et al (8) found modifications of serotonergic receptor concentrations in the brains of aggressive dogs. In response, Van den Berg et al (152) evaluated four serotonergic genes with respect to aggressive behavior in golden retrievers. Using mutation screens, linkage analysis, association studies, and quantitative genetic analysis, no obvious associations were found.…”
Section: Canine Behaviormentioning
confidence: 99%
“…Serpell and Hsu [26] found the factors consistent for dogs of various breeds and either sex in regard to behavioral traits in guide dogs. Furthermore, Hsu and Serpell developed a questionnaire (Canine behavioral assessment and research questionnaire: C-BARQ) for measuring behavioral traits in pet dogs by using data of 2,054 dogs in the United States [11], and this has been used as the behavioral index in gene studies about behavioral traits of dogs [15,31]. C-BARQ, which evaluates a dog's behavior objectively, can be a powerful tool for screening dogs for behavior problems and in evaluating the clinical effects of various treatments for behaviors [10,29,32].…”
mentioning
confidence: 99%